2021
DOI: 10.3390/pathogens10091156
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Characteristics of Escherichia coli Isolated from Patients with Urinary Tract Infections in a Medical Center at a Ten-Year Interval

Abstract: Escherichia coli causing urinary tract infections (UTIs) are one of the most common outpatient bacterial infections. This study aimed to compare the characteristics of E. coli isolated from UTI patients in a single medical center in 2009–2010 (n = 504) and 2020 (n = 340). The antimicrobial susceptibility of E. coli was determined by the disk diffusion method. PCRs were conducted to detect phylogenetic groups, ST131, K1 capsule antigen, and 15 virulence factors. Phylogenetic group B2 dominated in our 2009–2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…From the hands-on time and cost point of view, this workflow seems a reasonable approach for the surveillance of emerging clones. As reported in different studies, the phylogenetic group B2 is the predominant within UTI isolates, even though other seven E. coli phylogroups sensu stricto appear represented to a greater or lesser extent ( 18 , 33 , 37 , 38 ). Among the 59 different PG-CH combinations determined in our study, 11 E. coli clones comprised 46% of the 100 uUTI isolates.…”
Section: Discussionsupporting
confidence: 57%
“…From the hands-on time and cost point of view, this workflow seems a reasonable approach for the surveillance of emerging clones. As reported in different studies, the phylogenetic group B2 is the predominant within UTI isolates, even though other seven E. coli phylogroups sensu stricto appear represented to a greater or lesser extent ( 18 , 33 , 37 , 38 ). Among the 59 different PG-CH combinations determined in our study, 11 E. coli clones comprised 46% of the 100 uUTI isolates.…”
Section: Discussionsupporting
confidence: 57%
“…Among the seven phylogroups, phylogroup B2 was the most prominent phylogroup that accounted for 63.8% of the UPEC isolates (Table 1 and Table 2). This observation resembled the previous findings in Southeast Asia countries (e.g., Thailand and Vietnam), East Asia countries (e.g., Taiwan, Mongolia and Korea) and European countries (e.g., Romania, Germany and France) (Ramos et al, 2012;Toval et al, 2014;Lavigne et al, 2016;Munkhdelger et al, 2017;Cristea et al, 2019;Tewawong et al, 2020;Hyun et al, 2021;Lin et al, 2021b).…”
Section: Discussionsupporting
confidence: 90%
“…Little research emphasised the interactions between the bacterial traits and the host factors, especially for host age (Lin et al, 2021a). Although recent studies have demonstrated that the UPEC strains isolated from elderly patients showed greater antimicrobial resistance and conferred less VGs (Lin et al, 2021a;2021b), these works were constrained to a specific geographical area. More literature is needed to clarify the relationships between the bacterial traits of the UPEC strains and the host factors.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was waived because of the retrospective nature of the study, the isolates were remnants from patient samples, and the analysis used anonymous clinical data. A total of 844 non-duplicate E. coli isolates were identified in the clinical laboratory by colony morphology, Gram stain, biochemical tests, and the Vitek system (bioMérieux, Marcy l'Etoile, France) according to the manufacturer's recommendations [ 12 ]. E. coli isolates were stored at − 80 °C in lysogeny broth (LB) containing 20% glycerol (v/v) until tested.…”
Section: Methodsmentioning
confidence: 99%